2016
DOI: 10.1136/bmjopen-2015-010869
|View full text |Cite
|
Sign up to set email alerts
|

Investigating kidney donation as a risk factor for hypertension and microalbuminuria: findings from the Swiss prospective follow-up of living kidney donors

Abstract: ObjectivesTo assess the role of nephrectomy as a risk factor for the development of hypertension and microalbuminuria.DesignProspective, long-term follow-up study.SettingSwiss Organ Living-Donor Health Registry.ParticipantsAll living kidney donors in Switzerland between 1993 and 2009.InterventionsData on health status and renal function before 1 year and biennially after donation were collected.Primary and secondary outcome measuresComparison of 1-year and 5-year occurrences of hypertension among normotensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 34 publications
1
32
0
1
Order By: Relevance
“…There are conflicting data concerning the development of hypertension in humans with reduced renal mass: Our observations of arterial normotension after early uninephrectomy are in line with several clinical studies showing no significantly increased incidence of arterial hypertension in individuals born with a solitary kidney or in kidney donors 20 , 21 . On the other hand, there are also several clinical studies, which describe an increased risk for the development of hypertension in children with a solitary kidney 5 , 22 or in kidney donors 23 . The reasons for the discrepancies in study outcomes regarding blood pressure are still unclear, but might reflect different study designs or differences in the selection of the study collective.…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting data concerning the development of hypertension in humans with reduced renal mass: Our observations of arterial normotension after early uninephrectomy are in line with several clinical studies showing no significantly increased incidence of arterial hypertension in individuals born with a solitary kidney or in kidney donors 20 , 21 . On the other hand, there are also several clinical studies, which describe an increased risk for the development of hypertension in children with a solitary kidney 5 , 22 or in kidney donors 23 . The reasons for the discrepancies in study outcomes regarding blood pressure are still unclear, but might reflect different study designs or differences in the selection of the study collective.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed the presence of microalbuminuria in 12.12% of the sample. It has recently been demonstrated that nephrectomy in kidney donors increases the occurrence of microalbuminuria and susceptibility to hypertension‐induced microalbuminuria in this group of patients (Thiel et al ). Microalbuminuria is an early marker of glomerular injury (National Kidney Foundation Kidney Disease Outcomes Quality Initiative ), and most studies with long‐term follow‐up of living kidney donors have reported the presence of microalbuminuria in these patients (Gossmann et al ; Von Zur‐Muhlen et al .…”
Section: Discussionmentioning
confidence: 95%
“…However, most have limitations in long‐term compliance. One successful program is the Swiss Organ Living Donor Health Registry, which has provided data on postdonation incidence of hypertension and microalbuminuria . Despite the government‐mandated coverage of biennial medical follow‐up testing and a funded central donor registry, 10‐year follow‐up data were reported for only 65% of living donors .…”
Section: The Current State Of Living Donor Follow‐upmentioning
confidence: 99%
“…One successful program is the Swiss Organ Living Donor Health Registry, which has provided data on postdonation incidence of hypertension and microalbuminuria . Despite the government‐mandated coverage of biennial medical follow‐up testing and a funded central donor registry, 10‐year follow‐up data were reported for only 65% of living donors . The Australia/New Zealand Dialysis and Transplant Living Kidney Donor Registry is another program that has collected long‐term data on living kidney donors since 2004.…”
Section: The Current State Of Living Donor Follow‐upmentioning
confidence: 99%